Destabilisation of Creeping Permafrost: The Plator Rock Glacier Case Study (Central Italian Alps) - Scotti, R; Crosta, G; Villa, Alberto (Permafrost and Periglacial Processes, 2017)
The Plator rock glacier is the first such landform identified in the Italian Alps that shows destabilised behaviour. Analysis of six sets of sequential orthophotographs from 1981 to 2012 reveals an exceptional advance of the rock glacier front (92.1 m) and a horizontal velocity up to 4 m a-1 in different zones. The spatial variability of kinematics was evaluated by tracking sets of ‘tracer’ boulders on the rock glacier through time. Its velocity has progressively increased from the rooting zone to the tongue, with complex trends associated with distinct morphological features. Destabilisation likely occurred between 1954 and 1981, probably due to the relatively low elevation of the tongue, which resulted in warm permafrost conditions. Field observations reveal the presence of a large rock fall deposit, which occurred before 1981, and suggest that the debris overload could have triggered destabilisation. Since June 2015, an intensive monitoring programme has been implemented on the rock glacier, as the tongue is expected to travel over a steeper slope segment within the next 3 to 5 years, which could evolve in a catastrophic movement. Copyright © 2016 John Wiley & Sons, Ltd.